Psychological and Romantic Ideas - Syarif Hidayat; Aneira Maharani; Agustinus Hariyana; Nurul Fitriani (Pioneer: Journal of Language and Literature, 2023)
Telling a story about mental problems of teenagers, the novel All the Bright Places was adapted into a film with several differences in characterization, setting, and theme. The purpose of this study is to analyze the comparison of character and characterization of life and death instincts in the novel and film All the Bright Places. Furthermore, this study also aims to reveal different ideas through this adaptation. A qualitative descriptive method, adaptation theory by Hutcheon & O’Flynn, and Freud’s theory of life and death instinct were used in this research. By comparing the novel and film and using Freud's theory and adaptation theory, it shows that there is a life and death instinct in Finch's character that is different between the novel and the film. The novel shows more death instinct to show the message of adolescent psychological problems, while the film shows more life instinct with the aim of emphasizing the romantic side. In conclusion, through this adaptation analysis, there are differences in ideas or themes between the novel and the film All the Bright Places. The novel emphasizes the theme of adolescent mental problems while the film emphasizes the problem of teenage romance.